Protective activity of Malus doumeri leaf extract on H2O2-induced oxidative injury in H9C2 rat cardiomyocytes - Shen, Yi; Shen, Zheng; Li, Ping; Chen, Zhangrong; Wei, Bo; Liu, Danan; Si, Xiaoyun; Pan, Jiayi; Wu, Daiqin; Li, Wei (Frontiers in Cardiovascular Medicine, 2022)
In this study, Malus Doumeri leaf extract (MDLE) was used to test its anti-oxidation capacity in vitro, it has been preliminarily analyzed for H2O2-induced oxidative damage in H9C2 cells and its main active components. The antioxidant capacity through DPPH (1, 1-Diphenyl-2-Picrylhydrazyl), ABTS+• (2,2,2'-azino-BIS-(3-ethylbenzo-thiazoline-6-sulfonic acid) radical ion, •OH (hydroxyl radical), and •O2- (superoxide anion) were determined in vitro. The proliferation of H9C2 cells was examined by MTT (3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-Tetrazolium bromide). MDA (malondialdehyde), SOD (superoxide dismutase), CAT (catalase), GSH (glutathione), and GSH-Px (glutathione peroxidase) were determined by colorimetry. Apoptosis induced by oxidative damage was detected by flow cytometry. The mRNA expression of antioxidant related genes of SOD, CAT, GSH, and GSH-Px were checked by qRT-PCR (quantitative real-time polymerase chain reaction). The MDLE main active components were analyzed by HPLC (high-performance liquid chromatography). MDLE had significant scavenging effects on DPPH, ABTS+•, •OH, and superoxide anion radicals in a concentration-dependent manner. H2O2 treatment could significantly lead to oxidative stress injury of H9C2 cells, and MDLE treatment significantly improved the degree of H9C2 cell damage, and showed a positive correlation with concentration. MDLE can also reduce apoptosis caused by oxidative damage. MDLE treatment could significantly reduce MDA content and increase CAT, SOD, GSH, and GSH-Px contents and expression. In addition, by HPLC analysis, the following six bioactive components were detected from MDLE: chlorogenic acid, isoquercitrin, quercetin, baicalin, and phloretin. Therefore, MDLE has a good protective effect on myocardial cells.